2005
DOI: 10.1136/adc.2005.076141
|View full text |Cite
|
Sign up to set email alerts
|

Parental consent in paediatric clinical research

Abstract: Aims: To assess parental understanding and memorisation of the information given when seeking for consent to their child's participation to clinical research, and to identify the factors of significant influence on parents' decision making process. Methods: Sixty eight parents who had been approached for enrolling their child in a clinical oncology or HIV study were asked to complete an interview. Their understanding was measured by a score which included items required to obtain a valid consent according to F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 11 publications
4
52
2
4
Order By: Relevance
“…Perceived personal benefits from medical exams and treatment, and avoiding illness by being vaccinated as part of the trial were also found to be motivators, which is comparable to findings from Australia, 26 US, [28][29][30]35,39,40 and Europe. 27,31,32,36,42 Study participants confirmed they were at risk for dengue and thought a dengue vaccine would be beneficial. However, most would not participate and almost all would not allow their children to participate in a dengue vaccine trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived personal benefits from medical exams and treatment, and avoiding illness by being vaccinated as part of the trial were also found to be motivators, which is comparable to findings from Australia, 26 US, [28][29][30]35,39,40 and Europe. 27,31,32,36,42 Study participants confirmed they were at risk for dengue and thought a dengue vaccine would be beneficial. However, most would not participate and almost all would not allow their children to participate in a dengue vaccine trial.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Contributing factors to recruitment and retention include lack of trust, inadequate knowledge, fear of side effects and risks, and clinical trial procedures. 25,26,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Although studies have been conducted to understand cultural barriers to participation and retention in clinical trials, none have been conducted in Puerto Rico. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] In addition, formative research regarding factors related to participation in placebo controlled, vaccine trials is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…31,32,55,65 However, the relationship between anxiety, vulnerability and trial decisions may be mediated or moderated by factors such as trust in medical research 66 and the parent-practitioner relationship. 23,56,[67][68][69][70] The practicalities of trial participation are less commonly mentioned; 71 this may reflect the fact that most studies have been conducted in neonatology and oncology, when the child is usually in hospital at the time of the trial approach.…”
Section: Influences On Parents' Decision To Enter Their Child Into a mentioning
confidence: 99%
“…Particularly common worries for parents when considering a trial are that their child might be randomised to the treatment arm that they perceive to be less effective 50,55 and the responsibility that they would feel if the child later deteriorated. 56 Nevertheless, parents do perceive several benefits of trial participation for their own child, such as receiving extra medical attention. [57][58][59][60] Such benefits can be influential in their decision.…”
Section: Influences On Parents' Decision To Enter Their Child Into a mentioning
confidence: 99%
“…7,[12][13][14] In a study by Chappuy in which the parents were asked about their knowledge regarding the items included in the informed consent document, only a minority (21%) of parents were found to fully understand all items. 15 …”
Section: Parental Informed Consentmentioning
confidence: 99%